Risk and Risk Management Disclosure Among Malaysian Companies - Nor Shafinaz, Shaffee (2007)
The objectives of this study are to examine the current state of risk and risk management disclosures in annual reports in Malaysia and also to examine the association between risk and risk management disclosures and agency variables (namely size, profitability, leverage, risk, board composition and audit committee). This study used data from 97 main board companies for the year 2005. This study found that the highest risk disclosure is information for decision making and the lowest is environment risk. In terms of industry, property industry reported the highest volume of risk and risk management disclosures while, the lowest disclosure is displayed by technology companies. The risk and risk management characteristics occurring most frequently is of 'qualitative/past' type and the least disclosed is of 'quantitative/future' type. It is also found that there is greater disclosure of past information as compared to future information. This study also found that there is a positive and significant association between size and risk disclosure, and between size and overall risk and risk management disclosures. It is also found that there is a positive and significant association between firm profitability and audit committee with the extent of risk management disclosures. In contrast, other variables (namely, risk, leverage and board composition) are found to be statistically insignificant and have no association with the extent of risk and risk management disclosures.